Capacidad jurídica en el nuevo artículo 3 del Código Civil - Torres Vásquez, Aníbal (2020)
In this article, the author makes a deep analysis on the legal treatment that the Law has given to the human being in order to be a holder of rights and duties. He argues that the legal system, being in charge of recognizing the rights of individuals, can limit or deprive certain rights in order to safeguard a peaceful civil social coexistence. Likewise, the author establishes that, since our country is a party to the Convention on the Rights of Persons with Disabilities and in the interest of building a fair and respectful society, it is essential that the State guarantees the necessary legal and political adaptations so that persons with disabilities can realize themselves as persons with full rights.